2024
DOI: 10.1021/acs.macromol.3c01646
|View full text |Cite
|
Sign up to set email alerts
|

Clustering Effects on the Structure of Ionomer Solutions: A Combined SANS and Simulations Study

Chathurika Kosgallana,
Manjula Senanayake,
Supun S. Mohottalalage
et al.

Abstract: Ionic assemblies, or clusters, determine the structure and dynamics of ionizable polymers and enable their many applications. Fundamental to attaining well-defined materials is controlling the balance between the van der Waals interactions that govern the backbone behavior and the forces that drive the formation of ionic clusters. Here, using small-angle neutron scattering and fully atomistic molecular dynamics simulations, the structure of a model ionomer, sulfonated polystyrene in toluene solutions, was inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…In the f = 0.09 solutions, well-defined clusters are observed, and the polymer rich domains become denser and often segregated from the toluene. This significant phase segregation between the polymer-rich and solvent domains as has been previously reported by SANS . This inherent inhomogeneous in these associative systems drives the complex dynamics observed in S ( q,t ) .…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…In the f = 0.09 solutions, well-defined clusters are observed, and the polymer rich domains become denser and often segregated from the toluene. This significant phase segregation between the polymer-rich and solvent domains as has been previously reported by SANS . This inherent inhomogeneous in these associative systems drives the complex dynamics observed in S ( q,t ) .…”
Section: Resultssupporting
confidence: 73%
“…SPS in toluene above the overlap concentration for polystyrene forms a network driven by concentration fluctuations and formation of clusters. The structure of SPS in melts and solutions have been studied by numerous groups. ,, An example of the small angle scattering (SANS) pattern of SPS with f = 0.03 in toluene is given in Figure , where the very low q range depicts the signature of an instantaneous network and the intermediate q range captures the signature of an interionic correlations, often referred to as the “ionic peak”. Note that in contrast of SANS patterns of melts, for these low sulfonation levels, the interionic correlations are expressed in the line shape of the pattern.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the premise that the polar environment impacts the clusters, Weiss and co-workers have shown direct correlations between the nature of the counterion and the structure and rheology of these polymers. We have recently shown that the addition of small amounts of ethanol to SPS ionomers in toluene solutions decreases the average cluster size and increases the dynamics of the system. , However, further addition of ethanol collapses the chains, and the dynamics of the system decreases. These studies suggest that polar solvents with a relatively high solubility index, which will prevent the collapse of the polymer backbone but with a dielectric constant high enough to tweak the cohesion of the ionic clusters, would enhance the dynamics of ionomer melts.…”
Section: Introductionmentioning
confidence: 99%